The project to understand and research preterm pregnancy outcomes and stillbirths in South Asia (PURPOSe): a protocol of a prospective, cohort study of causes of mortality among preterm births and stillbirths - Elizabeth M. McClure; Sarah Saleem; Shivaprasad S. Goudar; Sangappa Dhaded; G. Guruprasad; Yogesh Kumar; Shiyam Sunder Tikmani; Masood Kadir; Jamal Raza; Haleema Yasmin; Janet L. Moore; Jean Kim; et al. (BMC, 2018)
Abstract Background In South Asia, where most stillbirths and neonatal deaths occur, much remains unknown about the causes of these deaths. About one-third of neonatal deaths are attributed to prematurity, yet the specific conditions which cause these deaths are often unclear as is the etiology of stillbirths. In low-resource settings, most women are not routinely tested for infections and autopsy is rare. Methods This prospective, cohort study will be conducted in hospitals in Davengere, India and Karachi, Pakistan. All women who deliver either a stillbirth or a preterm birth at one of the hospitals will be eligible for enrollment. With consent, the participant and, when applicable, her offspring, will be followed to 28-days post-delivery. A series of research tests will be conducted to determine infection and presence of other conditions which may contribute to the death. In addition, all routine clinical investigations will be documented. For both stillbirths and preterm neonates who die ≤ 28 days, with consent, a standard autopsy as well as minimally invasive tissue sampling will be conducted. Finally, an expert panel will review all available data for stillbirths and neonatal deaths to determine the primary and contributing causes of death using pre-specified guidance. Conclusion This will be among the first studies to prospectively obtain detailed information on causes of stillbirth and preterm neonatal death in low-resource settings in Asia. Determining the primary causes of death will be important to inform strategies most likely to reduce the high mortality rates in South Asia. Trial registration Clinicaltrials.gov (NCT03438110) Clinical Trial Registry of India (CTRI/2018/03/012281).